Efeito Casimir fermiônico na conjectura de violação da simetria de Lorentz do tipo Horava-Lifshitz - Silva, Dêivid Rodrigo da (2019)
In this thesis we analyze the consequences of the Lorentz violation in the fermionic Casimir effect. In this sense, we adopt the Horava-Lifshitz conjecture, which explicitly presents an asymmetry between temporal and spatial variables. We also adopt the massless fermionic field. The Casimir effect is constructed by assuming that the fermionic field is confined between two large parallel plates. This confinement is implemented through the MIT bag model on the plates. We find that the attractive or repulsive character of the Casimir force depends explicitly on the parameters associated with the considered Lorentz violation. The MIT bag condition was developed to confine fermions in the standard regime, however, we have shown that the same condition is adequate to confine the fermions that obey the modified Dirac equation. We also discuss the conservation of probability, finding the explicit expressions for the probability density and probability current of the model.